Liparis funingensis (Orchidaceae; Epidendroideae; Malaxidae), a new species from Yunnan, China: evidence from morphology and DNA - Su, Yong-Yu; Meng, Yuan; Shi, Yu; Tang, Guang-Da; Liu, Zhong-Jian (Phytotaxa, 2014)
A new orchid species, Liparis funingensis, from Yunnan, China, is described and illustrated in this study based on morphological and molecular analyses. A detailed comparison between the newly discovered orchid and other members of Liparis was performed. This new plant is characterized by an obovate lip and is trilobed. The sidelobes are semiorbicular and fleshy, and the midlobe is short and bilobed with triangular lobes. The disc has a deeply bilobed basal callus and two longitudinal lamellae from the base extending to above the middle. There are four pollinia in two pairs, with each pair exhibiting long caudicles without a viscidium. The rostellum also has a bursa synovialis. These features distinguish this new orchid from all other known species of Liparis. A phylogenetic analysis was subsequently performed to determine the systematic position of this enigmatic species. A molecular study based on nuclear ribosomal ITS and plastid matK DNA sequence data indicates that L. funingensis is a member of L. layardii subclade.